Pseudomonas aeruginosa proteolytically alters the interleukin 22-dependent lung mucosal defense. Issue 6 (18th August 2017) - Guillon, Antoine; Brea, Deborah; Morello, Eric; Tang, Aihua; Jouan, Youenn; Ramphal, Reuben; Korkmaz, Brice; Perez-Cruz, Magdiel; Trottein, Francois; O'Callaghan, Richard J.; Gosset, Philippe; Si-Tahar, Mustapha
ABSTRACT: The IL-22 signaling pathway is critical for regulating mucosal defense and limiting bacterial dissemination. IL-22 is unusual among interleukins because it does not directly regulate the function of conventional immune cells, but instead targets cells at outer body barriers, such as respiratory epithelial cells. Consequently, IL-22 signaling participates in the maintenance of the lung mucosal barrier by controlling cell proliferation and tissue repair, and enhancing the production of specific chemokines and anti-microbial peptides. Pseudomonas aeruginosa is a major pathogen of ventilator-associated pneumonia and causes considerable lung tissue damage. A feature underlying the pathogenicity of this bacterium is its capacity to persist and develop in the host, particularly in the clinical context of nosocomial lung infections. We aimed to investigate the ability of P. auruginosa to disrupt immune-epithelial cells cross-talk. We found that P. aeruginosa escapes the host mucosal defenses by degrading IL-22, leading to severe inhibition of IL-22-mediated immune responses. We demonstrated in vitro that, protease IV, a type 2 secretion system-dependent serine protease, is responsible for the degradation of IL-22 by P. aeruginosa . Moreover, the major anti-proteases molecules present in the lungs were unable to inhibit protease IV enzymatic activity. In addition, tracheal aspirates of patients infected by P. aeruginosa contain protease IV activity which further results in IL-22 degradation. This so far undescribed cleavage of IL-22 by a bacterial protease is likely to be an immune-evasion strategy that contributes to P. aeruginosa -triggered respiratory infections.